Masculinity and the Mise en Scene: The Collected Works of Billy the Kid - Derksen, Celeste (Studies in Canadian Literature, 1995)
The "cracks" can be seen in the reconstruction of the ideology of Western masculinity in the Belfry Theatre’s 1993 production of The Collected Works of Billy the Kid by Michael Ondaatje and JoAnn McIntyre. The iconic Western male is presented as both ideal and critique. Derksen questions both the actors’ presentation of this icon (in certain scenes) and her own position as critic and concludes that both actors and critic are a nexus of multiple, often contradictory gender and sexual ideologies.